2022
DOI: 10.3389/fenvs.2022.965408
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the implementation of agroecological practices: Lessons drawn from the Aba-Garima watershed, Ethiopia

Abstract: The challenges to agroecological transitions are not the same for all farmers and implementation of agroecological practices in different locations could yield different results. With this consideration, this study was conducted in Aba-Garima watershed in northwestern Ethiopia to characterize the structure and activities of farming households and assess factors influencing the implementation and sustainability of agroecological practices. Data were collected from 218 households, 16 key informants, and 12 focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Poor farmers depend heavily on organic resources to restore soil fertility, as they do not have capacity to purchase inorganic fertilizers, so this might help restore soil organic carbon. In line with this, Mekuria et al (2022) indicated that household wealth was one of the factors influencing the implementation and the sustainable use of organic soil amendments, such as the addition of manure.…”
Section: Tablementioning
confidence: 73%
“…Poor farmers depend heavily on organic resources to restore soil fertility, as they do not have capacity to purchase inorganic fertilizers, so this might help restore soil organic carbon. In line with this, Mekuria et al (2022) indicated that household wealth was one of the factors influencing the implementation and the sustainable use of organic soil amendments, such as the addition of manure.…”
Section: Tablementioning
confidence: 73%